Amphiphilic Oxygenated Amorphous Carbon-Graphite Buckypapers with Gas Sensitivity to Polar and Non-Polar VOCs - Homaeigohar, Shahin (Nanomaterials, 2019)
To precisely control the emission limit of volatile organic compounds (VOCs) even at trace amounts, reactive nanomaterials of, e.g., carbon are demanded. Particularly, considering the polar/non-polar nature of VOCs, amphiphilic carbon nanomaterials with a huge surface area could act as multipurpose VOC sensors. Here, for the first time, a buckypaper sensor composed of oxygenated amorphous carbon (a-COx)/graphite (G) nanofilaments is developed. Presence of the oxygen-containing groups rises the selectivity of the sensor to polar VOCs, such as ethanol and acetone through formation of hydrogen bonding, affecting the electron withdrawing ability of the group, the hole carrier density, and, thus, the resistivity. On the other hand, the electrostatic interactions between the toluene aromatic ring and the pi electrons of the graphitic crystals cause a formation of charge-transfer complexes, which could be the main mechanism of high responsiveness of the sensor towards non-polar toluene. To the best of my knowledge, an amphiphilic carbon nanofilamentous buckypaper has never been reported for gas sensing, and my device sensing polar/non-polar VOCs is state of the art for environmental control.
CRIS-Team WoS Importer:2019-10-22

An electroactive alginate hydrogel nanocomposite reinforced by functionalized graphite nanofilaments for neural tissue engineering - Homaeigohar, Shahin; Tsai, Ting-Yu; Young, Tai-Hong; Yang, Hsin Ju; Ji, You-Ren (Carbohydrate Polymers, 2019)
To address the need to biodegradable, electroactive conduits accelerating nerve regeneration, here we develop a nanocomposite hydrogel made of alginate reinforced by citric acid functionalized graphite nanofilaments. The green, simple functionalization enhances the nanofillers distribution and their biocompatibility, as verified using mesenchymal stem cells in vitro. The uniformly distributed nanofilaments raise mechanical stability of the nanocomposite hydrogel versus the neat one up to three times. Also, the nanofilaments enable electrical contact and intercellular signaling thereby stimulating their biological activity. In vitro studies proved the biocompatibility of the nanocomposite hydrogel whereon PC12 cells proliferate and spread evidently. In vivo tests also supported applicability of the nanocomposite hydrogel for implantation within body, and the samples showed no adverse reaction and no inflammatory responses after 14 days. Conclusively, the results certify that the developed electroactive nanocomposite hydrogel is able to stimulate nerve generation and could be confidently used as a nerve conduit material.
CRIS-Team WoS Importer:2019-09-20

Antibacterial biohybrid nanofibers for wound dressings - Homaeigohar, Shahin; Boccaccini, Aldo R. (Acta Biomaterialia, 2020)
Globally, chronic wounds impose a notable burden to patients and healthcare systems. Such skin wounds are readily subjected to bacteria that provoke inflammation and hence challenge the healing process. Furthermore, bacteria induce infection impeding re-epithelialization and collagen synthesis. With an estimated global market of 20.4 billion by 2021, appropriate wound dressing materials e.g. those composed of biopolymers originating from nature, are capable of alleviating the infection incidence and of accelerating the healing process. Particularly, biopolymeric nanofibrous dressings are biocompatible and mostly biodegradable and biomimic the extracellular matrix structure. Such nanofibrous dressings provide a high surface area and the ability to deliver antibiotics and antibacterial agents locally into the wound milieu to control infection. In this regard, with the dangerous evolution of antibiotic resistant bacteria, antibiotic delivery systems are being gradually replaced with antibacterial biohybrid nanofibrous wound dressings. This emerging class of wound dressings comprises biopolymeric nanofibers containing antibacterial nanoparticles, nature-derived compounds and biofunctional agents. Here, the most recent (since 2015) developments of antibacterial biopolymeric nanofibrous wound dressings, particularly those made of biohybrids, are reviewed and their antibacterial efficiency is evaluated based on a comprehensive literature analysis. Lastly, the prospects and challenges are discussed to draw a roadmap for further progresses and to open up future research avenues in this area. Statement of Significance: With a global market of 20.4 billion by 2021, skin wound dressings are a crucial segment of the wound care industry. As an advanced class of bioactive wound dressing materials, natural polymeric nanofibers loaded with antibacterial agents, e.g. antimicrobial nanoparticles/ions, nature-derived compounds and biofunctional agents, have shown a remarkable potential for replacement of their classic counterparts. Also, given the expanding concern regarding antibiotic resistant bacteria, such biohybrid nanofibrous wound dressings can outperform classical drug delivery systems. Here, an updated overview of the most recent (since 2015) developments of antibacterial biopolymeric nanofibrous wound dressings is presented. In this review, while discussing about the antibacterial efficiency of such systems, the prospects and challenges are highlighted to draw a roadmap for further progresses in this area.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Antibacterial agent; Biohybrid; Electrospinning; Nanofiber; Wound dressing

Biomimetic biohybrid nanofibers containing bovine serum albumin as a bioactive moiety for wound dressing - Homaeigohar, Shahin; Monavari, Mahshid; Koenen, Benedict; Boccaccini, Aldo R. (Materials Science and Engineering C, 2021)
For the first time, a biohybrid nanofibrous wound dressing is developed via green electrospinning of a blend solution of bovine serum albumin (BSA) (1 and 3 wt%) and polycaprolactone (PCL). In such a system, the components are miscible and interact through hydrogen bonding between the carbonyl group of PCL and the amine group of BSA, as verified by ATR-FTIR. As a result, the biohybrid nanofibers show a superior elastic modulus and elongation (300% and 58%, respectively) compared with the neat PCL nanofibers. The included protein induces a hydrophilicity effect to the PCL nanofibers, notably at the higher BSA content (3 wt%). In contrast to the neat nanofibers, the biohybrid ones are bioactive and encourage formation of biominerals (made of amorphous calcium carbonate) on the surface, after immersion in simulated body fluid (SBF). Based on the WST-8 cell viability tests, NIH3T3 fibroblast cells were seen to properly interact with the biohybrid mats and to proliferate in their proximity. SEM images show that the cells largely adhere onto such nanofibers even more than they do on the neat ones and adopt a flattened and stretched shape. In addition, the live/dead assay and phalloidin/DAPI staining assay confirm large cell viability and normal cell morphology on the biohybrid nanofiber mats after 4 days incubation. Taken together, BSA/PCL nanofibers are able to offer optimum mechanical properties (elasticity) as well as mineralization which can potentially stimulate the wound healing process, and can be considered a suitable candidate for wound dressing applications.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Biohybrid; Electrospinning; Polycaprolactone; Protein; Wound dressing

Bovine Serum Albumin (BSA)/polyacrylonitrile (PAN) biohybrid nanofibers coated with a biomineralized calcium deficient hydroxyapatite (HA) shell for wound dressing - Homaeigohar, Shahin; Tsai, Ting Yu; Zarie, Eman S.; Elbahri, Mady; Young, Tai Horng; Boccaccini, Aldo R. (Materials Science and Engineering C, 2020)
Here, for the first time, a nanofibrous (NF) wound dressing comprising biomineralized polyacrylonitrile (PAN) nanofibers is developed. In contrast to the majority of the currently available nanofibrous wound dressings that are based on natural polymers, PAN is a synthetic, industrial polymer, which has been rarely considered for this purpose. PAN NFs are first hydrolyzed to allow for tethering of biofunctional agents (here Bovine Serum Albumin (BSA)). Later, the biofunctionlized PAN NFs are biomineralized by immersion in simulated body fluid (SBF). As a result, core-shell, calcium deficient hydroxyapatite (HA)/BSA/PAN nanofibers form, that are mechanically stronger (elastic modulus; 8.5 vs. 6 MPa) compared to the untreated PAN NFs. The biomineralized PAN NFs showed promising bioactivity as reflected in the cell biology tests with fibroblast and keratinocyte cells. Hs68 fibroblasts and HaCat keratinocytes were found to be more viable in the presence of the biomineralized NFs than when they were co-cultured with the neat PAN NFs. Such mechanical and biological characteristics of the biomineralized PAN NFs are favorable for wound dressing applications.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Biofunctionalization; Biomineralization; Nanofiber; Polyacrylonitrile (PAN); Wound dressing

The nanosized dye adsorbents for water treatment - Homaeigohar, Shahin (Nanomaterials, 2020)
Clean water is a vital element for survival of any living creature and, thus, crucially important to achieve largely and economically for any nation worldwide. However, the astonishingly fast trend of industrialization and population growth and the arisen extensive water pollutions have challenged access to clean water across the world. In this regard, 1.6 million tons of dyes are annually consumed. Thereof, 10%–15% are wasted during use. To decolorize water streams, there is an urgent need for the advanced remediation approaches involving utilization of novel materials and technologies, which are cost and energy efficient. Nanomaterials, with their outstanding physicochemical properties, can potentially resolve the challenge of need to water treatment in a less energy demanding manner. In this review, a variety of the most recent (from 2015 onwards) opportunities arisen from nanomaterials in different dimensionalities, performances, and compositions for water decolorization is introduced and discussed. The state-of-the-art research studies are presented in a classified manner, particularly based on structural dimensionality, to better illustrate the current status of adsorption-based water decolorization using nanomaterials. Considering the introduction of many newly developed nano-adsorbents and their classification based on the dimensionality factor, which has never been employed for this sake in the related literature, a comprehensive review will be presented.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Adsorption; Decolorization; Dye pollution; Nanomaterials; Water treatment

Water treatment with new nanomaterials - Homaeigohar, Shahin (Water, 2020)
The studies introduced in this special issue aim to provide a state-of-the-art vision for nanomaterials-based technology that could profit the water treatment industry. Given the expanding crisis of water shortages across the world, this perspective is invaluable and of paramount importance. No doubt, as the environmental challenges are going to be more complicated and to extend to as-yet unconsidered areas, we need to upgrade our facilities and knowledge to address them properly. Nanomaterials are indeed promising building blocks for such advanced technologies that enable them to purify water streams from complex pollutants in an energy, cost and time-effective manner. The focus of the (review and original research) articles collected in this issue is on various kinds of nanomaterials made of carbon, polymer, metal, and metal oxides (magnetic and photocatalyst), that are employed for adsorption and photodegradation of heavy metals and organic pollutants, respectively. Here, I briefly review the insights given in these precious studies and suggest new directions for future research in this field.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Adsorption; Ecotoxicology; Membrane; Nanohybrids; Nanomaterial; Photocatalysis; Water treatment